Updated Integrated Analysis of the Efficacy and Safety of Entrectinib in Locally Advanced or Metastatic ROS1 Fusion–Positive Non–Small-Cell Lung Cancer. Issue 11 (10th April 2021) - Dziadziuszko, Rafal; Krebs, Matthew G.; De Braud, Filippo; Siena, Salvatore; Drilon, Alexander; Doebele, Robert C.; Patel, Manish R.; Cho, Byoung Chul; Liu, Stephen V.; Ahn, Myung-Ju; Chiu, Chao-Hua; Farago, Anna F.; et al.
Abstract : PURPOSE: Genetic rearrangements of the tyrosine receptor kinase ROS proto-oncogene 1 ( ROS1 ) are oncogenic drivers in non-small-cell lung cancer (NSCLC). We report the results of an updated integrated analysis of three phase I or II clinical trials (ALKA-372-001, STARTRK-1, and STARTRK-2) of the ROS1 tyrosine kinase inhibitor, entrectinib, in ROS1 fusion–positive NSCLC. METHODS: The efficacy-evaluable population included adults with locally advanced or metastatic ROS1 fusion–positive NSCLC with or without CNS metastases who received entrectinib ≥ 600 mg orally once per day. Co-primary end points were objective response rate (ORR) assessed by blinded independent central review and duration of response (DoR). Secondary end points included progression-free survival (PFS), overall survival (OS), intracranial ORR, intracranial DoR, intracranial PFS, and safety. RESULTS: In total, 161 patients with a follow-up of ≥ 6 months were evaluable. The median treatment duration was 10.7 months (IQR, 6.4-17.7). The ORR was 67.1% (n = 108, 95% CI, 59.3 to 74.3), and responses were durable (12-month DoR rate, 63%, median DoR 15.7 months). The 12-month PFS rate was 55% (median PFS 15.7 months), and the 12-month OS rate was 81% (median OS not estimable). In 24 patients with measurable baseline CNS metastases by blinded independent central review, the intracranial ORR was 79.2% (n = 19; 95% CI, 57.9 to 92.9), the median intracranial PFS was 12.0 months (95% CI, 6.2 to 19.3), and the median intracranial DoR was 12.9 months (12-month rate, 55%). The safety profile in this updated analysis was similar to that reported in the primary analysis, and no new safety signals were found. CONCLUSION: Entrectinib continued to demonstrate a high level of clinical benefit for patients with ROS1 fusion–positive NSCLC, including patients with CNS metastases.